1999
DOI: 10.1007/s101030050037
|View full text |Cite
|
Sign up to set email alerts
|

Killing of the Yeast and Hyphal Forms of Candida albicans Using a Light-Activated Antimicrobial Agent

Abstract: Oral infections due to Candida albicans are a common occurrence in patients with acquired immunodeficiency syndrome (AIDS). The purpose of this investigation was to determine whether the yeast and hyphal forms of the organism could be killed using the light-activated antimicrobial agent toluidine blue O (TBO). Three variables were investigated: TBO concentration, laser light dose and pre-irradiation time (PIT). Irradiation with light from a helium neon (HeNe) gas laser used in conjunction with the photosensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
53
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 21 publications
8
53
0
7
Order By: Relevance
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 56%
“…These authors also verified photosensitization of C. albicans under conditions resembling those that would be encountered in vivo (in saliva, serum, saline, and broth at a pH ranging from 4.0 to 7.0). 41 Jackson et al 19 found that the hyphal form of C. albicans was more susceptible to photoinactivation, requiring a lower TBO concentration than the yeast form. The germ tube formation of C. albicans, a transition state from budding to hyphal cells and an essential phase to virulence, was also inhibited by PDT using MB (0.027 to 13.37 mM) and laser light (28 J/cm 2 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The focus is now mainly on the PDI of pathogenic or potentially pathogenic fungi like Aspergillus fumigatus (9), Trichophyton rubrum (36), and especially Candida albicans (3,5,15,41), which is a common inhabitant of the mouth, throat, digestive tract, and skin. In hosts with a compromised immune system it can become pathogenic (8,11).…”
mentioning
confidence: 99%
“…However, others showed that low concentrations of toluidine blue O produced optimal killing of Cryptococcus gattii. 24,53 Some other studies also found that increase in concentration of methylene blue may cause a decrease in number of colonies recovered after the irradiation.…”
Section: 51mentioning
confidence: 92%